Determination of the ²³⁸U concentration in concrete samples by registration of fission neutrons - Kasilov, V.I.; Kirichenko, V.V.; Kokhnyuk, К.S.; Noga, V.I. (Вопросы атомной науки и техники, 2001)
In the work was to carry out and to improve the fission elements content tests of techniques for the concrete samples analysis of weight up to 0.5 kgs. The basis of this technique is the active analysis. Researched samples were irradiated with flows of neutrons received on the basis of the electron linear accelerator. The neutrons induce fissions in the samples. Experiment was carried out at ELE - 300 NSC KIPT. The technique allowing expressly, with a sufficient degree of reliability is checked up in operation to define the contents ²³⁸U in concrete samples. Achieved in the given experiment sensitivity makes ~ 10 g of uranium in a sample.